Identify the Development of Regional Ecotourism Potential Palopo City is Geospatial Based - Andi Jumardi; Muhammad Ilyas; Aryadi Nurfalaq; Iin Karmila Putri (Politeknik Pariwisata Makassar, 2022)
The purpose of the research, identifying geographical conditions and potential tourist attractions, the social conditions of the surrounding community, the prospect of ecotourism development. Methods in this research qualitative approach with survey research with geospatial and SWOT-based geography review approach. The results of this study produced 6 thematic maps including topographic maps, geological maps, land type maps, slope slopes, tourist attraction distribution maps, and distribution maps of public facilities by containing information about the most influential geographical conditions in supporting the development of mungkajang area as an ecotourism area. Potential tourist attractions owned by the Mungkajang area there are 9 attractions scattered in the Mungkajang area by offering its attractions Latuppa area offers waterfall and bathing tours in the river stream, Kambo area offers tourism and bathing, murante area bathing waterboom and Mungkajang area offers camping and shelter attractions in addition to tourist attractions in Mungkajang area equipped with various public facilities available. in tourist attractions and those outside of tourist attractions in the Mungkajang area. The social conditions of the community include people who live in the location of the Mungkajang area have the same understanding of ecotourism, approval of the development of Mungkajang ecotourism, interest in the development of Mungkajang ecotourism. Mungkajang area development strategy as ecotourism with a geographical review approach that supports among location factors, relief factors, climate factors, biogeography factors, soil factors, water factors, geological factors, population factors, attractiveness factors, infrastructure factors, accommodation factors and facility service factors, while from the results of SWOT analysis of strategies that must be carried out to maintain the sustainability of natural wealth, involving the community, Working with government agencies, maximizing information technology, offering tourism potential different from others, providing complete facilities as needed by tourists and building good cooperation between the government, private sector and the public in the utilization of SDA that has the potential as a tourist attraction.